Are donor-conceived people willing to use donors themselves? Insights from individuals conceived via donor-assisted reproduction. Issue 9 (30th July 2022) - Siegel, D R; Sheeder, J; Kramer, W; Roeca, C
Abstract: STUDY QUESTION: Are donor-conceived people (DCP) willing to utilize donor gametes themselves if unable to conceive spontaneously? SUMMARY ANSWER: The majority of DCP would consider or are undecided about utilizing donor gametes and those who would consider the utilization are more likely to have been told about their donor-conceived origins at a young age by a family member and have overall positive experiences as a DCP. WHAT IS KNOWN ALREADY: DCP view their donor conception as an important part of their self-identity and many desire contact with genetically related individuals. Additionally, many believe that sperm donation should only be practiced if identifying information on the donor is provided. STUDY DESIGN, SIZE, DURATION: This was a cross-sectional study using a Web-based survey that was disseminated from 6 March to 15 August 2021. A total of 528 participants completed the questionnaire. PARTICIPANTS/MATERIALS, SETTING, METHODS: The researcher-created survey was sent to registered users of the Donor Sibling Registry (DSR) who were conceived via donor-assisted reproduction and were 18 years of age or older. The survey was optional and anonymous, and the main outcome measure was the willingness to use donated gametes if unable to spontaneously conceive. MAIN RESULTS AND THE ROLE OF CHANCE: Of the 528 participants who completed the survey, 40.2% (212/528) have or would consider using donor gametes themselves if unable to conceive spontaneously and 24.6% (130/528) were undecided. Those who had used or were undecided about the utilization were significantly younger (26 years vs. 31 years, P  < 0.001) and less likely to be married (32.7% vs. 47.3%, P  < 0.001) than those who would not consider using donor gametes. They were also less likely to self-identify as female (78.9% vs. 86.6%, P  = 0.03) but had no difference in sexual orientation ( P  = 0.13). Additionally, they were more likely to have known about their donor-conceived origins for more years (18 (0–50) vs. 11 (0–61), P  = 0.004), be informed by a family member (75.5% vs. 65.6%, P  = 0.001) and have overall positive feelings about being conceived using a donor (93.0% vs. 52.5%, P  < 0.001). LIMITATIONS, REASONS FOR CAUTION: A major limitation is that DSR participants may not be representative of all DCP. Additionally, analyzing the DCP who stated that they were undecided about using donor gametes into the 'would consider' group may be overestimating the openness to utilization in this group. WIDER IMPLICATIONS OF THE FINDINGS: The findings from this study give new insight for health care workers to further counsel patients who are considering using third-party reproduction by providing reassurance that the majority of their future children would consider similar means, if needed, to achieve their family-building goals. STUDY FUNDING/COMPETING INTEREST(S): Funding for this study was received from the Department of Obstetrics and Gynecology Division of Reproductive Endocrinology and Infertility, University of Colorado. All authors declare that there are no conflicts of interest to disclose. TRIAL REGISTRATION NUMBER: N/A.